A SCALE DEVELOPMENT STUDY TO DETERMINE PSYCHOSOCIAL EVALUATIONS FOR SEAFARERS - Umut Yanardağ; Sena Öksüz (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Seafarers who spend long periods at sea and therefore have little contact with life on land face various difficulties because of their strenuous working conditions. While identifying those challenges and carrying out psychosocial interventions has the potential to increase the psychosocial well-being of seafarers, there is no scale to determine the psychosocial risks that seafarers contend with in the course of their work. This study was conducted with the aim of identifying the elements of the psychosocial risks they face so such a scale can be developed. A preliminary form was prepared for that purpose. Once the validity reliability rate of the form was determined on the basis of feedback, it was submitted to 735 members of the Turkish Seafarers ' Union residing in Istanbul and the resultant data was analyzed with SPSS and AMOS. As a result of the exploratory factor analysis, 3 factors named “Psychological/Spiritual Problems”, “Problems Related to Family and Environment” and “Problems Related to Work Environment” and 26 items were determined. It was determined that the total variance explained was 60.02%. In the confirmatory factor analysis performed, the structure consisting of 26 items and 3 sub-dimensions provided good fit values. As a result, it was concluded that a 3-factor Psychosocial Evaluation Scale for Seafarers consisting of 26 items is a valid and reliable scale.